Predictive value of syncope in pulmonary embolism - E. A. Kurakina; D. V. Duplyakov; S. M. Khokhlunov; G. S. Kozupitsa (Кардиоваскулярная терапия и профилактика)
Aim. To assess the predictive value of syncope in the clinical course of pulmonary thromboembolism (PTE). Material and methods. The study included 117 PTE patients (62 men and 55 women; mean age 51,86±13,4 years). High and intermediate risk of fatal outcome was observed in 37 and 80 patients, respectively. In all participants, PTE diagnosis was verified by pulmonary artery (PA) computed tomography. All patients were divided into two groups: Group I (n=35) with syncope registered 1-30 days ago (median time 1 day) and Group II (n=82) without syncope. The groups were comparable by age, gender, time of the clinical onset, clinical risk of PTE, and PA pressure levels. However, in Group I patients, the prevalence of high risk of fatal outcome was twice as high as in Group II participants (45,7% vs. 25,6%; p=0,032). To compare the thrombolysis therapy (TLT) independent levels of in-hospital mortality, the two TLT-free subgroups – 1 (14 patients with syncope) and 2 (58 patients without syncope) – were identified. Results. Syncope was associated with massive PA embolism (60% in Group I vs. 39% in Group II; p=0,036), often accompanied by shock/ hypotension (49% vs. 28%, respectively; p=0,032). Group I patients required TLT twice as often as Group II subjects (p=0,001), which resulted in reduced in-hospital mortality levels among individuals with syncope (p=0,048). Overall, both groups did not differ significantly by the levels of in-hospital mortality, while syncope patients demonstrated a tendency towards increased mortality (14,2% and 8,5%; p=0,35). However, in the absence of TLT, mortality levels reached 28,5% (4/14) in Subgroup 1 and 8,6% (8/58) in Subgroup 2 (p=0,042). Conclusion. Syncope in patients with possible PTE should be regarded as a marker of high risk of in-hospital death, due to a high prevalence of embolism in the PA trunk and main branches. TLT could improve the inhospital prognosis. To clarify the issue of prognostic value of syncope in PTE, further studies are necessary.